Analisis Kesesuaian Lahan Untuk Bumi Perkemahan di Bukit Leuweunghejo Desa Ciwaru Kabupaten Sukabumi Provinsi Jawa Barat - Harsono, Tricahyono Nur; Latif, Sufyan Abdul; Marwah, Siti; Handayani, Nur Purwati (Jurnal Pendidikan Geografi Undiksha, 2024)
Land use is generally influenced by land capabilities and land location. This research aims to determine the suitability of land for a campground on Leuwenghejo Hill. For campground activities, land use is influenced by land suitability classes which are characterized by the presence of supporting and inhibiting factors such as land drainage, flood danger, permeability, slope, soil texture, loose rock, exposed rock, reachability of water sources, distance to settlements and areas. disaster. The method used is a descriptive method using primary and secondary data arranged into spatial data and processed using overlay and matching analysis. The research results show that the suitability of the Leuweunghejo hill land for camping grounds is mostly (98.9%) marginal (S3) with limiting factors, namely permeability, surface soil texture and distance to water sources. Meanwhile, 1.1% of unsuitable land (N) for campsites has very heavy inhibiting factors and high slopes, difficult access to areas, and is far from water sources. So, based on an analysis of the land on Leuweunghejo Hill, it is marginally suitable for establishing a camping area. Land with marginal suitability (S3) can be handled using tent installation techniques that involve making small water channels around the tent, deep and strong stakes, and creating water reservoirs.